Analysis of game meat production - Gabriela-Dalila Stoica (Agrarian Economy and Rural Development - Trends and Challenges. International Symposium. 13th Edition, 2022)
Game meat (wild meat) is constantly present in the European meat market, but a limited number of consumers are interested in its consumption, given the unique characteristics of meat from wild animals. Game meat production in Europe decreased almost 9 times in 2020, reaching a total production of about 13.5 thousand tons, while nationally there was a growing trend until 2017 when it recorded production of 4,544 tons, an increase of 12% compared to 2005. The purpose of this paper is to analyze the total production of game meat in national, European, and EU countries, as well as the analysis of the import and export of game meat from Romania, Europe, and the EU. The data used are provided by the International Food and Agriculture Organization (FAO) database, on the basis of which the mentioned indicators were analyzed.
Keywords: C10; Q10; Q23; 330; Game meat; Romania; Total Production; Import; Export